Therapy of epilepsy - Harsono Harsono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1995)
Effective treatment of epilepsy requires accurate diagnosis. This relies heavily on proper identification of seizure type. Successful drug therapy requires a proper understanding of medication half-life and indications.Accurate diagnosis cannot be established easily since diagnosis of epilepsy relies on history taking and most of the patients do not show any clinical abnormality. Furthermore, diagnosis of epilepsy needs details of seizure type. This may be more difficult to be identified because information on the patients/their relatives are insufficient. Meanwhile, problems related to anti-epileptic drugs comprise poor understanding of the drugs, anticonvulsant interactions, development of adverse drug reactions, boring and poor compliance in taking medicine. Continuing medical education is one of the methods to solve the problems.Psychosocial conditions may interfere the treatment. In addition, any physician who cares epileptic patients should have comprehensive understanding of the patients condition including his/her family. On the other hand, the patients and/or their relatives should have proper information concerning the diagnosis, therapy, and prognosis of epilepsy.Health Centers, particularly ,in the rural areas, should have sufficient competence to manage epileptic patients. Good referral system will improve the competence and the patients will get some advantages.Key words: epilepsy - correct diagnosis - continuing medical education - psychosocial conditions - health center